2014
DOI: 10.1371/journal.pone.0094106
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CEACAM8 Interacts with CEACAM1 Inhibiting TLR2-Triggered Immune Responses

Abstract: Lower respiratory tract bacterial infections are characterized by neutrophilic inflammation in the airways. The carcinoembryonic antigen-related cell adhesion molecule (CEACAM) 8 is expressed in and released by human granulocytes. Our study demonstrates that human granulocytes release CEACAM8 in response to bacterial DNA in a TLR9-dependent manner. Individuals with a high percentage of bronchial lavage fluid (BALF) granulocytes were more likely to have detectable levels of released CEACAM8 in the BALF than tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 30 publications
2
51
0
Order By: Relevance
“…Assuming that CEACAM6 and CEACAM8 can interact with CEACAM1 at high concentrations on the cell surface, they too have the potential to disrupt CEACAM1 signaling through formation of heterodimers. Furthermore, the CEACAM1/8 interaction has been shown to inhibit Toll-like receptor 2-triggered immune responses (37). Thus, CEACAM6 could potentially modulate Toll-like receptor-2 inhibition through its recruitment of CEACAM8.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that CEACAM6 and CEACAM8 can interact with CEACAM1 at high concentrations on the cell surface, they too have the potential to disrupt CEACAM1 signaling through formation of heterodimers. Furthermore, the CEACAM1/8 interaction has been shown to inhibit Toll-like receptor 2-triggered immune responses (37). Thus, CEACAM6 could potentially modulate Toll-like receptor-2 inhibition through its recruitment of CEACAM8.…”
Section: Discussionmentioning
confidence: 99%
“…Another human-specific receptor of the CEACAM family, CEACAM1, is expressed on human airway epithelium and inhibits the TLR2-triggered M. catarrhalis-induced immune responses of human airway epithelium in response to ligation with M. catarrhalis via its intracellular immunoreceptor tyrosine-based inhibition motif (ITIM) (45,48). However, the results of our study indicate that epithelially expressed hCEACAM5, which is glycosylphosphatidylinositol (GPI)-anchored and does not bear an intracellular signaling domain (12), does not modulate M. catarrhalis-induced proinflammatory immune responses in the murine airways.…”
Section: Discussionmentioning
confidence: 99%
“…CCR2 is involved in the recruitment of macrophages to inflammatory sites along a macrophage chemoattractant protein 1 (MCP1) gradient. CEACAM1 belongs to a family of intermediateaffinity cell adhesion molecules involved in a variety of immune modulatory functions, including cell-cell contact, immune cell activation, and survival (35,(42)(43)(44). In vitro chemotactic assays with MCP1 and sCEACAM8, the natural ligands for CCR2 and CEACAM1, respectively, showed that IgM memory B cells possess chemotactic activity toward both ligands (P < 0.001 and P < 0.01, respectively; Fig.…”
Section: Human Igm Memory B Cells Show Migration and Differentiation mentioning
confidence: 97%
“…Neutrophils are recruited to epithelial cells in injured or infected tissue by secretion of early cytokines. In this early inflammatory response, neutrophils become activated and participate in a multilayered immunomodulatory network, recruiting and directing local responses by secretion of catecholamines and multiple cytokines, including chemokine (C-C motif) ligand 2 (CCL2), soluble carcinoembryonic antigen cell adhesion molecule 8 (sCEACAM8), and IFN-γ (33)(34)(35).…”
Section: Cd27mentioning
confidence: 99%